Liquidity Management: Implications for Financial Performance of Deposit Money Banks (DMBs) in Nigeria - Wisdom, Okere; Chibuzo, Okeke Obiajulu; Ijeoma, Echeonwu Sandra; Celestine, Emili Eze; Oluwatobi, Rufai (Journal of Asian Business Strategy, 2021)
This research assessed the impact of liquidity management on the financial performance of quoted deposit money banks in Nigeria. Secondary data were gathered from the corporate annual reports and accounts of fifteen (15) Banks for eleven (11) years spanning from 2007 to 2017. The agency theory was the theoretical framework upon which this study was hinged. Both descriptive and inferential statistics were adopted as analytical tools for the data. The results indicate that there exists a significant association amid liquidity management and financial performance of Deposit Money Banks in Nigeria. In addition, there exists a significant difference in the profitability of the Deposit Money Banks before and after the adoption of Treasury Single Account (TSA) in Nigeria. The study recommends that Deposit Money Banks should employ good liquidity management to mechanisms for a good performance and the Deposit Money Banks should reorganize its internal financial system in order to adapt to changes within the new policy (TSA).